Penatalaksanaan Holistik Pasien Anak Usia 15 Tahun dengan Dermatitis Atopik melalui Pendekatan Dokter Keluarga di Wilayah Puskesmas Segala Mider - Dewi, Mega Endiana; Bulfiah, Siti Noor Fadilah; Karyus, Aila (Medula, 2024)
Atopic dermatitis (AD) is a skin disorder that often occurs in infants and children, characterized by itching, frequent relapses, and a characteristic distribution of lesions. Management of DA contained in the 5 pillars which include patient education, prevention and modification of precipitating factors, improvement of optimal skin barrier function, management of inflammatory skin disorders, and control of the itch-scratch cycle. The aim of this study is to apply the principles of family medicine services to patients and carry out holistic management based on the patient problem found with patient-centered approach, family focused, and community oriented based on Evidence Based Medicine. This study is a case report with Primary data obtained through history taking, physical examination and home visits to complete family, psychosocial and environmental data. Secondary data was obtained from the patient's medical record. The assessment is based on a holistic diagnosis from the beginning, process, and end of the study. The result is there are internal and external factors happened to tje patient.  After the intervention, there was an improvement of symptom. Then there is an increase in knowledge through pretest and posttest. After holistic management was carried out based on the problems identified through family doctor approach, there was an increase in symptom as well knowledge abaout the disease.